ANTARCTIC TEMPERATURE STUDIES UTILIZING HRIR DATA FROM NIMBUS I. - Kerman, William Oscar, Jr.; Frame, Don Dale (1966)
Eighty nine orbits of Nimbus I High Resolution Infrared (HRIR) data (August 28 - September 22, 1964) were analyzed and compared to data from the reporting stations on the continent of Antarctica. Out of 281 station reports containing all types of weather typical of the Antarctic, it was found that the surface temperature of stations reporting cloudless conditions correlated best with the HRIR temperatures interpreted from the HRIR film. This paper includes a discussion of the methods used and the difficulties encountered in extracting usable data from the low contrast HRIR pictures over a homogeneous ice and snow covered area. (Author)